2014
DOI: 10.1111/acel.12208
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative stress causes functional alterations in mouse urothelium via a TRPM8‐mediated mechanism: implications for aging

Abstract: The incidence of bladder conditions such as overactive bladder syndrome and its associated urinary incontinence is highly prevalent in the elderly. However, the mechanisms underlying these disorders are unclear. Studies suggest that the urothelium forms a ‘sensory network’ with the underlying innervation, alterations in which, could compromise bladder function. As the accumulation of reactive oxygen species can cause functional alterations with age, the aim of this study was to investigate whether oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Excessive ROS production occurs in many pathological conditions including inflammation and reperfusion after ischaemia, contributing to the pathogenesis of a variety of human diseases (Comhair and Erzurum, ). In the bladder, excess production of ROS is strongly implicated in overactive bladder syndrome, bladder obstruction and pathological conditions developed with age (Brading et al, ; Nomiya et al, ; Nocchi et al, ). Excessive chronic generation of ROS during ischaemia‐reperfusion causes suppression of detrusor muscle function, inhibition of bladder afferents and efferents, and patchy nerve degeneration in the detrusor in patients with bladder obstruction and in animal models of obstruction and over‐distension (Brading et al, ; Yu et al, ; Scheepe et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS production occurs in many pathological conditions including inflammation and reperfusion after ischaemia, contributing to the pathogenesis of a variety of human diseases (Comhair and Erzurum, ). In the bladder, excess production of ROS is strongly implicated in overactive bladder syndrome, bladder obstruction and pathological conditions developed with age (Brading et al, ; Nomiya et al, ; Nocchi et al, ). Excessive chronic generation of ROS during ischaemia‐reperfusion causes suppression of detrusor muscle function, inhibition of bladder afferents and efferents, and patchy nerve degeneration in the detrusor in patients with bladder obstruction and in animal models of obstruction and over‐distension (Brading et al, ; Yu et al, ; Scheepe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the bladder, TRPM8 channels are expressed in the urothelium and in sensory nerve fibres (Stein et al, ; Mukerji et al, ; Hayashi et al, ). In the urothelium, TRPM8 channels may respond to the increased levels of ROS associated with ageing (Nocchi et al, ). We found that 47% of capsaicin‐sensitive high threshold afferents were activated by the TRPM8 channel agonist icilin.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chan et al (2001) showed deficiency of the p45NF-E2 gene, which causes an accumulation of elevated levels of reactive oxygen intermediates in red blood cells. According to Nocchi et al (2014), one of the main symptoms of oxidative stress in mice is impaired bladder activity associated with the deterioration of contractile response. Under conditions of ROS overproduction induced by the addition of melamine to the diet of female mice, Dai et al (2015) reported ovarian damage in the form of abnormal oocyte maturation.…”
Section: Oxidative Stress In Laboratory Animalsmentioning
confidence: 99%
“…In agreement with this hypothesis, Nocchi et al [21] served that intravesical administration of H 2 O 2 in normal rats induced bladder overactivity, as shown by a reduction in the intercontraction interval between detrusor contractions. Also in rats, Homan et al [23] observed that a single intravesical injection of H 2 O 2 significantly increased the number of voids, which lasted up to 7 days.…”
Section: Aging Oxidative Stress and Inflammationmentioning
confidence: 53%